Analytical Hierarchy Process for Optimizing Engines Operation by Procurement Strategies: A Case Study - Resnamurti, Dhanang; Okdinawati, Liane (Indonesian Journal of Multidisciplinary Science, 2023)
This research aims to examine of finding best choice type of contract for supporting critical engines operation and performance (including for maintenance and repairment). The researchers used Multi Criterion Decision-Making method with tool of Analytical Hierarchy Process, which data gather from survey and sampling from practitioners. They also used simplification of contract types from critical variable of contract such as price, quality, and delivery criterion. Criterion acquired from Forum Group Discussion with Subject Matter Expert. The research discovered that existing contracts vary and still many cases of unplanned shutdown lack of support from spare parts and other supports as a product form existing contracts.